Protein Tyrosine Phosphatase Expression Profile of Rheumatoid Arthritis Fibroblast‐like Synoviocytes: A Novel Role of SH2 Domain–Containing Phosphatase 2 as a Modulator of Invasion and Survival. Issue 5 (23rd April 2013) - Stanford, Stephanie M.; Maestre, Michael F.; Campbell, Amanda M.; Bartok, Beatrix; Kiosses, William B.; Boyle, David L.; Arnett, Heather A.; Mustelin, Tomas; Firestein, Gary S.; Bottini, Nunzio
Abstract: Objective: The fibroblast‐like synoviocytes (FLS) in the synovial intimal lining of the joint are key mediators of inflammation and joint destruction in rheumatoid arthritis (RA). In RA, these cells aggressively invade the extracellular matrix, producing cartilage‐degrading proteases and inflammatory cytokines. The behavior of FLS is controlled by multiple interconnected signal transduction pathways involving reversible phosphorylation of proteins on tyrosine residues. However, little is known about the role of the protein tyrosine phosphatases (PTPs) in FLS function. This study was undertaken to explore the expression of all of the PTP genes (the PTPome) in FLS. Methods: A comparative screening of the expression of the PTPome in FLS from patients with RA and patients with osteoarthritis (OA) was conducted. The functional effect on RA FLS of SH2 domain–containing phosphatase 2 (SHP‐2), a PTP that was up‐regulated in RA, was then analyzed by knockdown using cell‐permeable antisense oligonucleotides. Results: PTPN11 was overexpressed in RA FLS compared to OA FLS. Knockdown of PTPN11, which encodes SHP‐2, reduced the invasion, migration, adhesion, spreading, and survival of RA FLS. Additionally, signaling in response to growth factors and inflammatory cytokines was impaired by SHP‐2 knockdown. RA FLS that were deficient in SHP‐2 exhibited decreased activation of focal adhesion kinase and mitogen‐activated protein kinases. Conclusion: These findings indicate that SHP‐2 has a novel role in mediating human FLS function and suggest that it promotes the invasiveness and survival of RA FLS. Further investigation may reveal SHP‐2 to be a candidate therapeutic target for RA.